2016
DOI: 10.3389/fnana.2016.00101
|View full text |Cite
|
Sign up to set email alerts
|

Individual Neurons Confined to Distinct Antennal-Lobe Tracts in the Heliothine Moth: Morphological Characteristics and Global Projection Patterns

Abstract: To explore fundamental principles characterizing chemosensory information processing, we have identified antennal-lobe projection neurons in the heliothine moth, including several neuron types not previously described. Generally, odor information is conveyed from the primary olfactory center of the moth brain, the antennal lobe, to higher brain centers via projection neuron axons passing along several parallel pathways, of which the medial, mediolateral, and lateral antennal-lobe tract are considered the class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(84 citation statements)
references
References 58 publications
16
68
0
Order By: Relevance
“…While the mlALT in dung beetles seems to connect specifically to the LH, the tALT bifurcates and appears to make connections also to the protocerebrum. These connection patterns are similar to those in Drosophila (Tanaka, Suzuki, et al, 2012) and Heliothis Ian, Zhao, et al, 2016).…”
Section: Antennal Lobesupporting
confidence: 76%
See 2 more Smart Citations
“…While the mlALT in dung beetles seems to connect specifically to the LH, the tALT bifurcates and appears to make connections also to the protocerebrum. These connection patterns are similar to those in Drosophila (Tanaka, Suzuki, et al, 2012) and Heliothis Ian, Zhao, et al, 2016).…”
Section: Antennal Lobesupporting
confidence: 76%
“…As in other species, the mALT was found to be the thickest ALT, and could be clearly distinguished from the rest by a strongly anti-5-HTimmunoreactive fiber. As in the noctuid moth H. virescens, the mALT in dung beetles seems to be the only ALT that directly connects the AL and the mushroom body calyx (CA) (Figure 9d-f; Ian, Zhao, Lande, & Berg, 2016). As in the noctuid moth H. virescens, the mALT in dung beetles seems to be the only ALT that directly connects the AL and the mushroom body calyx (CA) (Figure 9d-f; Ian, Zhao, Lande, & Berg, 2016).…”
Section: Antennal Lobementioning
confidence: 99%
See 1 more Smart Citation
“…Contralateral neurons of the type reported here (Fig. 9E) have only been noted occasionally in Manduca sexta (Homberg et al, 1988), H. virescens (Ian et al, 2016a) and another noctuid species, Agrotis segetum (Wu et al, 1996). Our results indicate that the contralateral neuron follows the v-lALT before sending a branch toward the margin of PED with the main axon turning toward the midline.…”
Section: Discussionsupporting
confidence: 60%
“…Rø et al (2007) reported a similar l-lcPN with sparse dendritic arborizations in several glomeruli from a female H. virescens indicating that the d-lALT pathway is not restricted to pheromone processing in males. Another such l-lcPN was reported by Ian et al (2016a) although it was not clear if this neuron was stained in a female or male H. virescens.…”
Section: Discussionmentioning
confidence: 96%